Injectable hydrogel for promoting white fat browning by cooperating with photothermal and preparation method and application of injectable hydrogel

By loading ursolic acid nanoparticles on the mesoporous polydopamine surface and adding it to an injectable hydrogel, OCMU hydrogel is formed, and combined with photothermal treatment, the problem of lack of effective inducing browning of white adipose tissue in the prior art is solved, and long-term efficient treatment of obesity and improvement of metabolic disorders is achieved.

CN119792188AInactive Publication Date: 2025-04-11WENZHOU INST UNIV OF CHINESE ACAD OF SCI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510020420.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art lacks effective and sustainable induction strategies to promote the browning of white adipose tissue and thus solve the problem of obesity, and ursolic acid is limited by its inability to dissolve in water, low permeability and low bioavailability.

Method used

The nanodrug carrier is formed by loading ursolic acid nanoparticles on the mesoporous polydopamine surface and adding the carrier to the injectable hydrogel prepared from self-assembly to form a hydrogel (OCMU hydrogel) loaded with mesoporous polydopamine nanoparticles to induced fat reduction in conjunction with photothermal treatment.

Benefits of technology

Long-term and efficient treatment of obesity is achieved and obesity-related metabolic disorders are improved. By inducing browning of white adipose tissue, the accumulation of adipose tissue is significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119792188A_ABST
    Figure CN119792188A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of injectable hydrogel for promoting white fat browning by cooperating with light and heat, which comprises the following steps: S1, respectively dissolving mesoporous polydopamine and ursolic acid in absolute ethyl alcohol, uniformly mixing the mesoporous polydopamine and the ursolic acid, stirring for a period of time in a dark place, centrifuging, and collecting precipitate to obtain UA-loaded MPDA nanoparticles marked as MPDA-coated UA; s2, mixing an amido-containing raw material A, the MPDA prepared in the step S1 and an aqueous solution to obtain a solution I; mixing an aldehyde group-containing raw material B with an aqueous solution to obtain a solution II; and mixing the two components to prepare the injectable hydrogel. The injectable hydrogel prepared by the invention can be used for inducing fat reduction in cooperation with photothermal treatment, promoting white fat browning, realizing long-term efficient treatment on obesity and improving metabolic disorders related to obesity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to an injectable hydrogel that promotes browning of white fat in a synergistic manner using photothermal energy, and a preparation method and application thereof. Background Art

[0002] In recent years, the incidence and prevalence of obesity and its related metabolic diseases have continued to rise, becoming a major challenge facing the global health care system. Although lifestyle interventions (such as adjusting diet and increasing exercise) have played a certain role in weight control, their effects are often limited and difficult to maintain in the long term. At the same time, drug therapy and surgical procedures also have side effects that cannot be ignored. Therefore, it is particularly urgent to explore novel, efficient and long-term stable obesity treatment strategies.

[0003] The core problem of obesity is the excessive accumulation of white adipose tissue. It is worth noting that white adipose tissue has the potential to transform into beige fat through the browning process, which can promote energy consumption and reduce fat accumulation. This mechanism not only provides new ideas for improving obesity, but also points out the direction for the development of innovative anti-obesity drugs.

[0004] Although browning of white fat is a potential method to curb obesity, there is still a lack of effective and sustainable induction strategies in clinical practice. Ursolic acid (UA) is a natural pentacyclic triterpenoid active compound widely found in plants, fruits and herbs. Many studies have confirmed that it has good anti-obesity activity and the ability to induce browning of white adipose tissue. Although ursolic acid has significant advantages as a potential drug for the treatment of obesity, in practical applications, ursolic acid is limited by its poor solubility in water, low permeability and low bioavailability. This is also a common application problem of terpenoid compounds and a key breakthrough direction for future research and development.

[0005] In recent years, photothermal therapy has been rapidly developed and applied because of its harmlessness, non-invasiveness and low side effects on tissues. In particular, near-infrared light (NIR) is widely used in cancer treatment and skin regeneration because it can penetrate the skin deep into the subcutaneous layer. The latest research shows that local photothermal therapy can also activate beige fat, showing significant effects on the prevention and treatment of obesity in mice without causing any adverse reactions. Combining natural compounds with photothermal therapy can be a potential new solution to promote the browning of white fat to treat obesity.

[0006] There are currently no reports on the synergistic application of ursolic acid and near-infrared light in the treatment of obesity. Summary of the invention

[0007] Based on the above-mentioned defects in the prior art, the present invention discloses a method for preparing an injectable hydrogel that synergizes photothermal treatment to promote the browning of white fat. The prepared injectable hydrogel can synergize with photothermal treatment to induce fat loss, promote the browning of white fat, achieve long-term and efficient treatment of obesity, and improve obesity-related metabolic disorders.

[0008] The specific technical solutions are as follows:

[0009] A method for preparing an injectable hydrogel that promotes browning of white fat by synergistic photothermal therapy comprises the following steps:

[0010] S1. Dissolve mesoporous polydopamine and ursolic acid in anhydrous ethanol respectively, mix them evenly, and then stir them in the dark for a period of time. Collect the precipitate by centrifugation to obtain MPDA nanoparticles loaded with UA, which are recorded as MPDA@UA.

[0011] S2, mixing the amino group-containing raw material A, the MPDA@UA prepared in step S1 and the aqueous solution to obtain solution I; mixing the aldehyde group-containing raw material B and the aqueous solution to obtain solution II; and mixing the two to prepare the injectable hydrogel, which is denoted as OCMU hydrogel.

[0012] The preparation method disclosed in the present invention uses mesoporous polydopamine as a raw material, namely as a photothermal conversion agent, and also as a carrier for loading ursolic acid to solve the application limitations of ursolic acid due to its poor solubility in water, low permeability and low bioavailability, and then uses an amine-containing raw material A and an aldehyde-containing raw material B to self-assemble through a Schiff base reaction to form a stable hydrogel, and finally adds the prepared UA-loaded MPDA nanoparticles into the hydrogel to prepare a hydrogel of mesoporous polydopamine nanoparticles loaded with ursolic acid (OCMU hydrogel).

[0013] In step S1:

[0014] Mesoporous polydopamine can be prepared according to the method in the literature (Peng L, Peng H, Li W, Zhao D. Monomicellar assembly to synthesize structured and functional mesoporous carbonaceous nanomaterials. Nat Protoc. 2023Apr; 18(4): 1155-1178. doi: 10.1038 / s41596-022-00784-6.).

[0015] Preferably, the concentration of the prepared mesoporous polydopamine / anhydrous ethanol solution is 0.1 to 10 mg / mL; more preferably 1 to 5 mg / mL; and more preferably 2 mg / mL.

[0016] Preferably, the concentration of the prepared ursolic acid / anhydrous ethanol solution is 0.1 to 10 mg / mL; more preferably 1 to 5 mg / mL; and more preferably 2 mg / mL.

[0017] Preferably, the mass ratio of mesoporous polydopamine to ursolic acid is 1:(0.125-8); more preferably, the mass ratio of mesoporous polydopamine to ursolic acid is 1:(1-4).

[0018] The UA loading amount in the prepared MPDA@UA nanoparticles can be controlled by adjusting the mass ratio of mesoporous polydopamine and ursolic acid.

[0019] In step S1:

[0020] Preferably, the stirring is carried out at room temperature in a dark environment at a speed of 100 to 500 r / min;

[0021] After the centrifugal collection, washing and drying are required;

[0022] Preferably, the drying is selected from freeze drying.

[0023] In step S2:

[0024] Preferably, the amino-containing raw material A is selected from one or more of carboxymethyl chitosan, quaternized chitosan, and N-succinyl chitosan; more preferably, it is carboxymethyl chitosan.

[0025] Preferably, the concentration of the amino-containing raw material A in the solution I is 1 to 100 mg / mL; more preferably 30 to 80 mg / mL;

[0026] Preferably, the mass ratio of the amino-containing raw material A to MPDA@UA is (0.25-100):1;

[0027] More preferably, the mass ratio of the amine-containing raw material A to MPDA@UA is (10-50):1.

[0028] Preferably, the aldehyde-containing raw material B is selected from one or more of oxidized hyaluronic acid, oxidized sodium alginate, and oxidized chondroitin sulfate; more preferably, it is oxidized hyaluronic acid.

[0029] Preferably, the concentration of solution II is 1 to 100 mg / mL; more preferably 30 to 80 mg / mL;

[0030] More preferably, solution I and solution II are mixed at equal concentrations and volumes.

[0031] The concentration of MPDA@UA in the injectable hydrogel can be controlled by adjusting the mass of the amine-containing raw material A and MPDA@UA.

[0032] Preferably, the concentration of MPDA@UA in the injectable hydrogel is controlled to be 0.5-2.0 mg / mL;

[0033] More preferably, the concentration of MPDA@UA in the injectable hydrogel is controlled to be 0.5-1.5 mg / mL.

[0034] The present invention also discloses an injectable hydrogel prepared according to the above method for promoting the browning of white fat through synergistic photothermal treatment.

[0035] The hydrogel was confirmed to be injectable.

[0036] The invention also discloses the application of the injectable hydrogel in promoting the browning of white fat by synergistic photothermal treatment.

[0037] Preferably, the synergistic photothermal treatment uses near-infrared light with a wavelength of 650-900 nm and a power of 0.25-1.00 W / cm 2 .

[0038] Further preferred:

[0039] The concentration of MPDA@UA in the injectable hydrogel is 1 mg / mL;

[0040] Synergistic photothermal uses near-infrared light with a wavelength of 808nm and a power of 0.25W / cm 2 , time is 10 minutes.

[0041] Compared with the prior art, the present invention has the following advantages:

[0042] The present invention discloses a method for preparing an injectable hydrogel that synergistically promotes the browning of white fat by photothermal therapy. Ursolic acid nanoparticles are loaded on the surface of mesoporous polydopamine to form a nano drug carrier. The nano drug carrier is added to the injectable hydrogel prepared by self-assembly as a drug delivery system. The system has a synergistic effect of photothermal therapy while completing the delivery of ursolic acid. It is expected to achieve long-term and efficient treatment of obesity and improve obesity-related metabolic disorders by inducing the browning of white adipose tissue. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The scanning electron microscopy results of MPDA and MPDA@UA nanoparticles prepared in Example 1;

[0044] Figure 2 The transmission electron microscopy results of MPDA and MPDA@UA nanoparticles prepared in Example 1;

[0045] Figure 3 The particle size results of MPDA and MPDA@UA nanoparticles prepared in Example 1;

[0046] Figure 4 This is a diagram showing the injectability of the OCMU hydrogel prepared in Example 1;

[0047] Figure 5 The scanning electron microscopy results of the OC hydrogel, OCM hydrogel and OCMU hydrogel prepared in Comparative Examples 1 to 2 and Example 1, respectively;

[0048] Figure 6 The Oil Red O staining results and statistical results of mouse 3T3-L1 adipocytes for different hydrogels and different experimental groups with or without light treatment; A is the Oil Red O staining picture, and B is the Oil Red O extraction result picture; *** P<0.001, compared with the Control group; ### P < 0.001, compared with the corresponding NIR-group;

[0049] Figure 7 The results of triglyceride content in mouse 3T3-L1 adipocytes for different experimental groups with different hydrogels and whether or not they were treated with light; * P<0.05, compared with the Control group; # P < 0.05, compared with the corresponding NIR-group;

[0050] Figure 8 The expression results of the browning gene UCP1 in mouse 3T3-L1 adipocytes for different hydrogels and different experimental groups with or without light treatment; ** P<0.01, compared with the Control group; # P<0.05, ## P < 0.01, compared with the corresponding NIR-group;

[0051] Fig. 9 The results of the weight changes of mice in different experimental groups with different hydrogels and whether or not they were treated with light; *** P < 0.001, compared with PBS group;

[0052] Fig.10 Results of subcutaneous fat tissue weight of mice in different experimental groups with different hydrogels and whether or not they were treated with light; * P<0.05, compared with the Control group; ## P < 0.01, compared with the corresponding NIR group; Fig.11 HE staining results of subcutaneous inguinal adipocytes of mice and statistical results of adipocyte size for different experimental groups with different hydrogels and whether or not they were treated with light; A is the HE staining result, and B is the adipocyte size statistics; *** P<0.001, compared with the Control group;

[0053] ### P < 0.001, compared with the corresponding NIR-group;

[0054] Fig.12 The following are the results of immunohistochemical staining of UCP1 in subcutaneous inguinal fat of mice and the statistics of positive results for different experimental groups with different hydrogels and whether or not they were treated with light; A is the result of immunohistochemical staining of UCP1, and B is the statistics of positive expression of UCP1; *** P<0.001, compared with the Control group;

[0055] ## P<0.01, ### P < 0.001, compared with the corresponding NIR-group. DETAILED DESCRIPTION

[0056] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the following embodiments are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0057] The abbreviations used in the present invention are explained in Table 1 below:

[0058] Table 1

[0059]

[0060] Example 1

[0061] S1: Preparation of mesoporous polydopamine nanoparticles loaded with ursolic acid

[0062] 50mL of ethanol and 50mL of deionized water were mixed at 500 rpm for 1min by a magnetic stirrer to obtain an ethanol-water mixture. 1g of Pluronic F127 was added to the ethanol-water mixture, and after continuous stirring for 15min, 1mL of 1,3,5-trimethylbenzene was added, and after ultrasonication to form a white emulsion, magnetic stirring was continued for 15min. 750mg of dopamine hydrochloride was weighed and added to the above solution, and stirring was continued for another 10min. 1.5mL of ammonia water was slowly added and stirring was continued in the dark. After 3h, the mesoporous polydopamine (MPDA) sample was collected by centrifugation (11600r / min, 10min), and then washed once with ethanol and deionized water respectively, and freeze-dried for 24h for use.

[0063] First, 2 mg of MPDA and 2 mg of UA were dissolved in 1 mL of anhydrous ethanol, and the two were mixed evenly and stirred at 300 r / min for 24 h at room temperature and in the dark. The precipitate was collected by centrifugation (12000 r / min, 20 min), washed twice with anhydrous ethanol, and freeze-dried for later use to obtain MPDA nanoparticles loaded with UA, which were recorded as MPDA@UA. The UA loading in the MPDA@UA prepared in this example was 36.2% as measured and calculated by a UV spectrophotometer.

[0064] The morphology of mesoporous polydopamine (MPDA) and mesoporous polydopamine loaded with ursolic acid (MPDA@UA) was tested by scanning electron microscopy and transmission electron microscopy. Figure 1 and Figure 2 , indicating that: MPDA nanoparticles have a clear spherical morphology and uniform size distribution. Mesoporous structure can be observed on the surface of the particles. After loading UA, scanning electron microscopy and transmission electron microscopy showed that the morphology of MPDA@UA remained intact, but the mesoporous structure was reduced, indicating that UA was successfully loaded on MPDA. The particle size analysis of mesoporous polydopamine (MPDA) and mesoporous polydopamine loaded with ursolic acid (MPDA@UA) was performed, and the results are as follows Figure 3 , indicating that after loading with UA, the diameter of MPDA increased from 226nm to 241nm.

[0065] S2: Preparation of OCMU hydrogel

[0066] Carboxymethyl chitosan (CMCS) was dissolved in ultrapure water to prepare a 60 mg / mL CMCS aqueous solution, and the MPDA@UA prepared in step S1 was added to the CMCS aqueous solution to control its concentration to 2 mg / mL; oxidized hyaluronic acid (OHA) was dissolved in ultrapure water to prepare an OHA aqueous solution with a concentration of 60 mg / mL; the two were mixed at 37°C in equal volumes to prepare a hydrogel, which was recorded as OCMU hydrogel. In the hydrogel, the concentration of MPDA@UA was 1 mg / mL.

[0067] The successfully prepared OCMU hydrogel was loaded into a syringe ( Figure 4 A), then Figure 4 As shown in B, the hydrogel in the syringe was injected into the PBS aqueous solution to form a hydrogel. Figure 4 As shown in C, the hydrogel in the syringe was injected onto the culture dish. The above results demonstrated the injectability of OCMU hydrogel.

[0068] Comparative Example 1

[0069] Oxidized hyaluronic acid (OHA) was dissolved in ultrapure water to prepare an OHA aqueous solution with a concentration of 60 mg / mL; carboxymethyl chitosan (CMCS) was dissolved in ultrapure water to prepare a CMCS aqueous solution with a concentration of 60 mg / mL; the two were mixed in equal volumes at 37°C to prepare a hydrogel, which was recorded as OC hydrogel.

[0070] Comparative Example 2

[0071] S1: Preparation of mesoporous polydopamine nanoparticles

[0072] 50mL of ethanol and 50mL of deionized water were mixed at 500 rpm for 1min by a magnetic stirrer to obtain an ethanol-water mixture. 1g of Pluronic F127 was added to the ethanol-water mixture, and after continuous stirring for 15min, 1mL of 1,3,5-trimethylbenzene was added, and after ultrasonication to form a white emulsion, magnetic stirring was continued for 15min. 750mg of dopamine hydrochloride was weighed and added to the above solution, and stirring was continued for another 10min. 1.5mL of ammonia water was slowly added and stirring was continued in the dark. After 3h, the mesoporous polydopamine (MPDA) sample was collected by centrifugation (11600r / min, 10min), and then washed once with ethanol and deionized water respectively, and freeze-dried for 24h for use.

[0073] S2: Preparation of OCM hydrogel

[0074] Carboxymethyl chitosan (CMCS) was dissolved in ultrapure water to prepare a 60 mg / mL CMCS aqueous solution, and the MPDA prepared in step S1 was added to the CMCS aqueous solution to control its concentration to 2 mg / mL; oxidized hyaluronic acid (OHA) was dissolved in ultrapure water to prepare an OHA aqueous solution with a concentration of 60 mg / mL; the two were mixed at 37°C in equal volumes to prepare a hydrogel, which was recorded as OCM hydrogel. In the hydrogel, the concentration of MPDA was 1 mg / mL.

[0075] The pore structures of OC hydrogel, OCM hydrogel, and OCMU hydrogel were observed using scanning electron microscopy. Figure 5 As shown, the surface of OC hydrogel is relatively smooth, while the surfaces of OCM hydrogel and OCMU hydrogel are rough, in which MPDA and MPDA@UA are evenly distributed in the hydrogel.

[0076] Example 2

[0077] The preparation process is exactly the same as that of Example 1, except that in step S1, the mass of UA is replaced with 8 mg.

[0078] After testing, the UA loading amount in the MPDA@UA prepared in this example is 61.2%.

[0079] Example 3

[0080] The preparation process is exactly the same as that in Example 1, except that in step S2, the concentration of MPDA@UA in the CMCS aqueous solution is controlled to be 1 mg / mL; at this time, the concentration of MPDA@UA in the prepared OCMU hydrogel is 0.5 mg / mL.

[0081] Example 4

[0082] The preparation process is exactly the same as that in Example 1, except that in step S2, the concentration of MPDA@UA in the CMCS aqueous solution is controlled to be 3 mg / mL; at this time, the concentration of MPDA@UA in the prepared OCMU hydrogel is 1.5 mg / mL.

[0083] Example 5

[0084] The preparation process is exactly the same as that in Example 1, except that in step S2, the concentration of MPDA@UA in the CMCS aqueous solution is controlled to be 4 mg / mL; at this time, the concentration of MPDA@UA in the prepared OCMU hydrogel is 2 mg / mL.

[0085] The OCMU hydrogels prepared in Examples 1 and 3 to 5 were studied at 808 nm and 0.5 W / cm 2 The temperature changes under NIR irradiation at different times were monitored by an infrared thermal imager and the temperature data were recorded, which are listed in Table 2 below.

[0086] Table 2

[0087]

[0088] The temperature changes of the OCMU hydrogel (MPDA@UA concentration of 1 mg / mL) prepared in Example 1 under NIR irradiation of different powers at 808 nm for different times were further studied, and the temperature data were recorded and listed in Table 3 below.

[0089] Table 3

[0090]

[0091] Comparing the data in Table 2 and Table 3, it can be seen that the concentration of MPDA@UA in OCMU hydrogel can be set to 1 mg / mL, and the power of the near-infrared light used in the synergistic photothermal treatment can be set to 0.25 W / cm 2 , the irradiation time was set to 10min.

[0092] Performance Test:

[0093] 1. Cell test:

[0094] Mouse 3T3-L1 adipocytes were cultured in a DMEM medium containing 10 vol% fetal bovine serum at 37°C and 5 vol% CO2 incubator. After the cells were fully grown, they were cultured for 2 days (this time was marked as day 0), and treated with DMEM containing 10 vol% fetal bovine serum, 5 μg / mL insulin, 1 μM dexamethasone and 0.5 mM IBMX for 2 days to induce adipogenic differentiation. After induction of differentiation, the culture medium was changed to a differentiation maintenance medium containing 10 vol% fetal bovine serum and insulin, which was replaced every 2 days. Then, the culture was continued for 2 days with a maintenance medium without insulin, and the cells were completely differentiated into mature adipocytes on the 8th day. The mature adipocytes were treated with the sterile OC hydrogel, OCM hydrogel and OCMU hydrogel prepared in Comparative Examples 1, 2 and Example 1, respectively, for 12 hours, and then irradiated with 808 nm laser (0.25 W / cm 2 , 10min), and Oil Red O staining was performed after further treatment for 2 hours. The control group was the anhydrous gel group.

[0095] The results are as follows Figure 6 As shown: before photothermal treatment (NIR-), compared with the control group, the lipid droplet size of the OC and OCM groups did not change, while the intracellular lipid droplet size of the OCMU group was significantly reduced; after photothermal treatment of each group, the lipid content in the adipocytes of the OCM+NIR group and the OCMU+NIR group was significantly reduced, confirming that both UA and NIR can cause fat decomposition and provide fuel for fat thermogenesis.

[0096] The triglyceride content of the treated mature adipocytes was measured using a triglyceride kit. Figure 7 As shown: Before photothermal treatment (NIR-), the triglyceride content of cells decreased significantly after OCMU treatment compared with the control group. The decrease in triglyceride content was also found in the OCM and OCMU groups after NIR treatment.

[0097] The key genes of browning were detected by qRT-PCR. Figure 8 As shown: Compared with the OCM group, the UCP1 gene expression in the OCM group after NIR treatment was significantly increased, and compared with the control group, the UCP1 gene expression in the OCMU group was also significantly increased, and after adding NIR treatment, the UCP1 gene content further increased. The above results show that both UA and NIR can induce the browning of adipocytes, and these two induction methods have a synergistic effect.

[0098] 2. Animal experiments:

[0099] 80 6-week-old C57BL6 / J male mice (about 22g) were selected and fed with 60% kcal high-fat diet for 8 weeks to construct a high-fat diet obesity model (body weight exceeded 20% of mice in the normal feeding group). There were 10 mice in the normal group, which were fed with maintenance diet. After the model was successfully established, the high-fat group was randomly divided into PBS group, PBS+NIR group, OC group, OC+NIR group, OCM group, OCM+NIR group, OCMU group, OCMU+NIR group, with 10 mice in each group. The specific treatment plan for each group is as follows:

[0100] ①PBS group and PBS+NIR group: 100 μL PBS was injected subcutaneously bilaterally in the groin of mice.

[0101] The NIR group was irradiated with 808 nm laser (0.25 W / cm 2 , 10 min, for 3 consecutive days); ②OC group and OC+NIR group: 100 μL OC hydrogel was injected subcutaneously bilaterally in the groin of mice. After injection, the NIR group was irradiated with 808 nm laser (0.25 W / cm 2 , 10 min, for 3 consecutive days); ③ OCM group and OCM+NIR group: 100 μL OCM hydrogel (Comparative Example 2) was injected subcutaneously in the groin of mice on each side, where the MPDA concentration was 1 mg / mL. After injection, the NIR group was irradiated with 808 nm laser (0.25 W / cm 2 , 10 min, for 3 consecutive days);

[0102] ④OCMU group and OCMU+NIR group: 100 μL of OCMU hydrogel was injected subcutaneously in the groin of mice on each side, where the concentration of MPDA@UA was 1 mg / mL (Example 4, containing 61.2 wt% UA). After injection, the NIR group was irradiated with 808 nm laser (0.25 W / cm 2 , 10 min, for 3 consecutive days). The above treatment was performed once a week for 2 weeks. The mice were weighed every week during the experiment. Fig. 9 The results showed that the untreated mice gained about 4% of their body weight in two weeks, while the OCM and OCMU groups lost 10% and 11% of their body weight after NIR treatment. In addition, the OCMU group also lost 4% of its body weight. The above proves that NIR and UA have significant therapeutic effects on obesity.

[0103] On day 14, the mice were euthanized, and the inguinal white adipose tissue (iWAT) was isolated and weighed. Fig.10 The results showed that the amount of iWAT fat in UA-treated mice was significantly reduced compared with the control group. The accumulation of adipose tissue was also significantly reduced after NIR treatment.

[0104] In addition, HE staining was performed on the inguinal white adipose tissue. Fig.11 The results showed that both UA and NIR could reduce the size of adipocytes induced by a high-fat diet.

[0105] UCP1 immunohistochemical staining was further performed on inguinal white adipose tissue. Fig.12 The results showed that compared with the control group, the expression level of UCP1, a key factor of browning, was significantly increased after UA and NIR treatment. At the same time, compared with the OCMU group without NIR treatment, the expression level of UCP1 in the OCMU group after NIR treatment was significantly increased, indicating that NIR and UA have obvious synergistic effects.

Claims

1. A method for preparing an injectable hydrogel that promotes browning of white fat by synergistic photothermal therapy, characterized in that: The steps include: S1. Dissolve mesoporous polydopamine and ursolic acid in anhydrous ethanol respectively, mix them evenly, and then stir them in the dark for a period of time. Collect the precipitate by centrifugation to obtain MPDA nanoparticles loaded with UA, which are recorded as MPDA@UA. S2. Mix the amino-containing raw material A, the MPDA@UA prepared in step S1 and the aqueous solution to obtain solution I; mix the aldehyde-containing raw material B and the aqueous solution to obtain solution II; and mix the two to prepare the injectable hydrogel, which is denoted as OCMU hydrogel.

2. The method for preparing the injectable hydrogel for promoting the browning of white fat by synergistic photothermal treatment according to claim 1, characterized in that: In step S1: The concentration of the prepared mesoporous polydopamine / anhydrous ethanol solution is 0.1-10 mg / mL; The concentration of the prepared ursolic acid / anhydrous ethanol solution is 0.1-10 mg / mL; The mass ratio of mesoporous polydopamine to ursolic acid is 1:(0.125-8).

3. The method for preparing the injectable hydrogel for promoting browning of white fat by synergistic photothermal treatment according to claim 1, characterized in that: In step S1: The stirring is carried out at room temperature in a dark environment at a speed of 100 to 500 r / min; After the centrifugal collection, washing and drying are required.

4. The method for preparing the injectable hydrogel for promoting browning of white fat by synergistic photothermal treatment according to claim 1, characterized in that: In step S2: The amino-containing raw material A is selected from one or more of carboxymethyl chitosan, quaternized chitosan, and N-succinyl chitosan; The concentration of the amino-containing raw material A in the solution I is 1 to 100 mg / mL; The mass ratio of the amino-containing raw material A to MPDA@UA is (0.25-100):

1.

5. The method for preparing the injectable hydrogel for promoting browning of white fat by synergistic photothermal treatment according to claim 1, characterized in that: In step S2: The aldehyde-containing raw material B is selected from one or more of oxidized hyaluronic acid, oxidized sodium alginate, and oxidized chondroitin sulfate; The concentration of the solution II is 1-100 mg / mL.

6. The method for preparing the injectable hydrogel for promoting browning of white fat by synergistic photothermal treatment according to claim 1, characterized in that: In step S2: The concentration of the amino-containing raw material A in the solution I is 30-80 mg / mL; The concentration of the solution II is 30-80 mg / mL.

7. The method for preparing an injectable hydrogel for promoting browning of white fat in synergistic photothermal reaction according to any one of claims 1 to 6, characterized in that: In step S2, the concentration of MPDA@UA in the injectable hydrogel is 0.5-2.0 mg / mL.

8. An injectable hydrogel prepared by the method according to any one of claims 1 to 7 for promoting the browning of white fat through synergistic photothermal treatment.

9. Use of the injectable hydrogel according to claim 8 in promoting the browning of white fat in a synergistic manner using photothermal therapy.

10. Use of the injectable hydrogel according to claim 9 in promoting browning of white fat in synergistic photothermal treatment, characterized in that: Synergistic photothermal uses near-infrared light with a wavelength of 650-900nm and a power of 0.25-1.00W / cm 2 .

Citation Information

Patent Citations

  • Preparation method and application of targeting mesoporous polydopamine nanoparticles

    CN117379563A